Development of manufacturing key performance indicators for Malaysian Small and Medium Industries (SMIS) - Anuar, A.; Mohd. Yusuff, Rosnah; Megat Ahmad, Megat Mohamad Hamdan; Abdul Aziz, M. (2005)
The coming decade will see survival and success of an economy determined by its ability to maintain and sustain its competitiveness. Benchmarking has been identified as an effective management tool for improving productivity and quality, thus enhance competitiveness. It is a systematic and continuous process of searching, learning, adapting and implementing the best practices worldwide towards attaining superior performance. Benchmarking encourages the culture of self-assessing and the initiative towards continuous improvement in knowledge, information and skill among participating companies. It is a key management technique, which can assist Malaysian SMIs, achieve their challenging targets and remain competitive in the years ahead. The paper discuss on the development of KPIs in manufacturing practices for SMIs. The relative importance of the KPIs was determined by sending questionnaires to Enterprise 50 award winners from 2000 – 2003. Enterprise 50 is an annual award programme that recognizes the achievement of Malaysian SMIs. The survey was conducted in eight areas, which are management, human resources development, technology and product innovation, financial and marketing strategy, quality, production process, supply chain management, and customer focus. Among the elements of KPI identified, customer focus is the most important followed by management, quality, supply chain, production process, financial and market strategy, human resource development and technology and product innovation as the least important. It is hoped that this study will provide some insights into the companies’ performance in each of the areas and help them in improving their practices.